Two's company, three's a crowd: Food and shelter limitation outweigh the benefits of group living in a shoaling fish. Issue 5 (1st May 2013) - Ford, John R.; Swearer, Stephen E.
Abstract : Identifying how density and number‐dependent processes regulate populations is important for predicting population response to environmental change. Species that live in groups, such as shoaling fish, can experience both direct density‐dependent mortality through resource limitation and inverse number‐dependent mortality via increased feeding rates and predator evasion in larger groups. To investigate the role of these processes in a temperate reef fish population, we manipulated the density and group size of the shoaling species Trachinops caudimaculatus on artificial patch reefs at two locations with different predator fields in Port Phillip Bay, Australia. We compared mortality over four weeks to estimates of predator abundance and per capita availability of refuge and food to identify mechanisms for density or number dependence. Mortality was strongly directly density dependent throughout the experiment, regardless of the dominant predator group; however, the limiting resource driving this effect changed over time. In the first two weeks when densities were highest, density‐dependent mortality was best explained by refuge competition and the abundance of benthic predators. During the second two weeks, food competition best explained the pattern of mortality. We detected no effect of group size at either location, even where pelagic‐predator abundance was high. Overall, direct density effects were much stronger than those of group size, suggesting little survival advantage to shoaling on isolated patch reefs where resource competition is high. This study is the first to observe a temporal shift in density‐dependent mechanisms in reef fish, and the first to observe food limitation on short temporal scales. Food competition may therefore be an important regulator of postsettlement reef fish cohorts after the initial intense effects of refuge limitation and predation.